Evaluation Of Implementation Of Kkni-Based Curriculum In Christian Religious Education Study Program Using The Cippo Model: Study Of The Quality Of Implementation Of Christian Religious Education At The Kupang State Christian Institute – East Nusa Tenggar (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to evaluate the implementation of the KKNI-based PAK curriculum implemented at IAKN Kupang. Based on its characteristics, this research is classified as evaluative research. Thus, the method used is the evaluative analysis method with the CIPPO model. This evaluation model is an acronym for Context (C), Input (I), Process (P), Product (P), and Outcomes (O). Data collection was carried out through rating scales, interviews, distributing questionnaires, and reviewing evaluated curriculum documents by involving seven (7) lecturers involved in curriculum preparation, the head of the PAK study program, and 186 PAK graduates from 2019 to 2021.The evaluation results show that the implementation of the KKNI-based PAK curriculum implemented by the PAK study program of IAKN Kupang lacks good quality preparation criteria when viewed from the context, input, process, product, and outcome components. The updated curriculum has several weaknesses, so overall, it is concluded that the preparation, updating, and development of the PAK curriculum at IAKN Kupang is not based on good and ideal preparation criteria, so this situation has an impact on the quality of PAK implementation that is not on target.